FOOD PRACTICES AND INTRODUCTION OF COMPLEMENTARY FEEDING OF INFANTS EXPOSED TO VERTICAL TRANSMISSION OF HIV - Queiroz, Priscila Marino; Lemos, Paula Cunha; Ued, Fábio da Veiga (Journal of Health Care, 2017)
Introduction: The impossibility of breastfeeding by HIV positive mothers contributes to changes in the dietary pattern of their children in the first months of life. Objective: To analyze the feeding practices of infants exposed to HIV, checking the type of feeding practiced by the mothers, the dilution and preparation of the milk offered, the period and the way of introduction of complementary feeding, as well as the food groups offered to infants. Materials and methods: A cross-sectional, descriptive study performed with children aged 6 to 24 months. The data were obtained through semi-structured interview and medical records. Results: All infants (n=32) started infant formula after birth, however, 18.8% of mothers diluted the formula incorrectly. There was no report of breastfeeding, but 59.4% of the children received cow milk before 12 months of life. In 31.2% of cases complementary feeding was introduced before the sixth month, and foods such as eggs, fish, and vegetables were not offered to all children. In addition, industrialized foods sources of simple carbohydrates, sodium, and fat were introduced since the fifth month. Conclusions: The replacement of breast milk for infant formulas was adequate. However, there was inadequacy in the dilution of the formulas, inopportune introduction of cow milk and complementary food, reduced supply of legumes, meat, eggs, vegetables, and inappropriate consumption of processed and/or ultraprocessed foods in the first months of life. Such practices contribute to changes in nutritional status and the development of noncommunicable chronic diseases.